ANALISIS IMPLEMENTASI KURIKULUM DAN PRINSIP BELAJAR DALAM TRANSFORMASI PENDIDIKAN DI ERA DIGITAL: STUDI KASUS PENGGUNAAN GAME-BASED LEARNING DI SD NEGERI PASARBATANG 03 - Nisriina Amiirah Faatin; Bambang Sumardjoko; Sabar Narimo (STKIP Subang, 2025)
This study aims to provide an in-depth analysis of curriculum implementation and learning principles in the era of digital transformation, with a focus on the use of interactive platforms as educational bridges. Amidst the rapid development of the Industrial Revolution 4.0, the world of education is required to adapt learning strategies that are not only content-relevant but also methodological. This study used a descriptive qualitative approach with a case study of 5th-grade students at Pasarbatang 03 Public Elementary School, Brebes Regency. Data were collected through participant observation, in-depth interviews, and curriculum document analysis. The results revealed that the synergy between flexible curriculum design and active learning principles significantly increased students' emotional and cognitive engagement. The integration of the Roblox platform as a Game-Based Learning (GBL) medium proved effective in visualizing abstract curriculum concepts, increasing learning interest by up to 93%, and strengthening students' multimodal literacy skills by up to 96.2%. However, the findings also indicated challenges in the form of potential disruption of focus and gaps in technology access. This study concluded that the effectiveness of a modern curriculum is highly dependent on the role of teachers as digital literacy navigators and internet ethics monitors. This research recommendation includes the need to develop standardized game-based teaching modules to support 21st-century learning principles.